Addressing Emotional Dysregulation Within NDBI for Young Autistic Children: Outcomes and Factors Related to Change - Elizabeth H. Kushner; Chloe B. Holbrook; Nicole M. Hendrix; Josie Dylan Douglas-Brown; Katherine E. Pickard (Behavioral Sciences)
Despite high rates of emotional dysregulation among autistic children, few studies have explored interventions addressing dysregulation. Naturalistic developmental behavioral interventions (NDBIs) are a class of interventions focused on supporting social communication. As social communication and emotion regulation skills emerge from similar developmental processes, NDBIs may be one approach for addressing dysregulation among autistic children. The present study sought to characterize change in dysregulation among one-hundred and eleven caregiver–child dyads completing Project ImPACT, a caregiver-mediated NDBI. Caregivers reported on child communication and social engagement using the Social Communication Checklist and emotion regulation using the Emotional Dysregulation Inventory-Young Child at the beginning and end of services. Clinicians reported on caregiver fidelity at each intervention session. Children showed reductions in emotional dysregulation throughout Project ImPACT, though reductions were specific to children who began the program with elevated dysregulation. Child social engagement at baseline and caregivers’ fidelity to specific strategies within Project ImPACT were associated with reductions in emotional dysregulation. Very few studies have tested interventions aimed at supporting emotion regulation among young autistic children. These findings demonstrate that NDBIs may support emotion regulation as well as social communication skills. Further incorporating support for emotion regulation in NDBI may address this critical gap without increasing service coordination for families.